2022
DOI: 10.5306/wjco.v13.i2.147
|View full text |Cite
|
Sign up to set email alerts
|

First-line cisplatin, docetaxel, and cetuximab for patients with recurrent or metastatic head and neck cancer: A multicenter cohort study

Abstract: BACKGROUND The targeted therapy cetuximab [directed at the epidermal growth factor receptor (EGFR)] in combination with 5-fluorouracil and platinum-based chemotherapy (the EXTREME regimen) has shown substantial efficacy for patients with recurrent or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). Thus, this scheme has been established as the preferred first-line option for these patients. However, more recently, a new strategy combining platinum, taxanes, and cetuximab (the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…A recent clinical trial comparing cetuximab-containing regimens that included platinum and 5-FU versus cisplatin and docetaxel found that individuals treated with the taxane-containing regimen had similar overall and progression-free survival compared to those receiving the 5-FU-containing, but fewer serious adverse events and better self-reported quality of life (17). Other studies have confirmed that cetuximab + cisplatin + docetaxel is a welltolerated regimen (18,19). Further research, including the final results of the KEYNOTE-B10 clinical trial, is needed to determine whether combining pembrolizumab with taxanes is also associated with reduced toxicity compared to 5-FU-containing combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent clinical trial comparing cetuximab-containing regimens that included platinum and 5-FU versus cisplatin and docetaxel found that individuals treated with the taxane-containing regimen had similar overall and progression-free survival compared to those receiving the 5-FU-containing, but fewer serious adverse events and better self-reported quality of life (17). Other studies have confirmed that cetuximab + cisplatin + docetaxel is a welltolerated regimen (18,19). Further research, including the final results of the KEYNOTE-B10 clinical trial, is needed to determine whether combining pembrolizumab with taxanes is also associated with reduced toxicity compared to 5-FU-containing combinations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be related to 5-FU's toxicity (particularly with respect to gastrointestinal side-effects) and patient inconvenience [i.e., the need for port placement and a 96-hour pump to administer the drug, and a requirement for dihydropyrimidine dehydrogenase deficiency testing before initiating treatment (12)]. Taxanes such as paclitaxel have been suggested as replacements for 5-FU in both pembrolizumab and cetuximab combination therapies for R/M HNSCC and have demonstrated encouraging performance in initial analyses (12)(13)(14)(15)(16)(17)(18)(19). Pembrolizumab in combination with cisplatin or carboplatin plus paclitaxel or docetaxel is currently listed as a category 2A option for 1L treatment of R/M HNSCC in the NCCN Guidelines ® (11), and thus is already available in the US.…”
Section: Introductionmentioning
confidence: 99%
“…A modified systemic 5-FU chemotherapy protocol was assessed with the aim of decreasing hospitalization and/or treatment time without compromising outcomes, which could increase the life quality of patients with metastatic squamous cell carcinoma of the head and neck (SCCHN) (Meirovitz et al., 2022 ). More recently, a new strategy using the immune checkpoint inhibitor pembrolizumab alone or in combination with 5-FU and platinum has become an appropriate first-line treatment for patients with recurrent or metastatic head and neck cancer (Falco et al., 2022 ). 5-FU is accessible to the relevant tissues in conjugation with the transport protein serum albumin (Chinnathambi et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%